Using Vodafone mobile phone network data to provide insights into citizens mobility in Italy during the Coronavirus outbreak. (15th September 2021) - Calabrese, Francesco; Cobelli, Enrico; Ferraiuolo, Vincenzo; Misseri, Giovanni; Pinelli, Fabio; Rodriguez, Daniel
Abstract: In this paper, we present the work conducted by Vodafone to enrich the understanding of people movement in Italy during the outbreak of the Coronavirus in 2020, and the tool developed to support the decisions taken by the authorities during that period. We have developed a solution to anonymously monitor the daily movements of Vodafone SIMs in Italy, at aggregate level, at different spatial and temporal granularity, to provide insights into the movements of Italians.